Physical activity and prenatal depression: going beyond statistical significance by assessing the impact of reliable and clinical significant change. Issue 4 (27th March 2021) - Vargas-Terrones, Marina; Nagpal, Taniya S.; Perales, Maria; Prapavessis, Harry; Mottola, Michelle F.; Barakat, Ruben
Abstract: Background: Previous literature supports exercise as a preventative agent for prenatal depression; however, treatment effects for women at risk for prenatal depression remain unexplored. The purpose of the study was to examine whether exercise can lower depressive symptoms among women who began pregnancy at risk for depression using both a statistical significance and reliable and clinically significant change criteria. Methods: This study is a secondary analysis of two randomized controlled trials that followed the same exercise protocol. Pregnant women were allocated to an exercise intervention group (IG) or control group (CG). All participants completed the Center for Epidemiological Depression (CES-D) scale at gestational week 9–16 and 36–38. Women with a baseline score ⩾16 were included. A clinically reliable cut-off was calculated as a 7-point change in scores from pre- to post-intervention. Results: Thirty-six women in the IG and 25 women in the CG scored ⩾16 on the CES-D at baseline. At week 36–38 the IG had a statistically significant lower CES-D score (14.4 ± 8.6) than the CG (19.4 ± 11.1; p < 0.05). Twenty-two women in the IG (61%) had a clinically reliable decrease in their post-intervention score compared to eight women in the CG (32%; p < 0.05). Among the women who met the reliable change criteria, 18 (81%) in the IG and 7 (88%) in the CG had a score <16 post-intervention, with no difference between groups ( p > 0.05). Conclusions: A structured exercise program might be a useful treatment option for women at risk for prenatal depression.